Associative Cognitive Factors of Math Problems in Students Diagnosed With Developmental Dyscalculia - Van Luit, Johannes Erik Harold; Toll, Sylke Wilhelmina Maria (Frontiers in Psychology, 2018)
The Dutch protocol, ‘Dyscalculia: Diagnostics for Behavioural Professionals’ (DDBP protocol; Van Luit, Bloemert, Ganzinga, & Mönch, 2014), describes how behavioural experts can examine whether a student has developmental dyscalculia (DD), based on three criteria: severity, discrepancy, and resistance. In addition to distinguishing the criteria necessary for diagnosis, the protocol provides guidance on formulating hypotheses by describing and operationalising four possible associative cognitive factors of math problems: planning skills, naming speed, short-term and/or working memory, and attention. The current exploratory and descriptive research aims to describe the frequency of these four primary associative cognitive factors in students with DD from the Netherlands. Descriptive data from 84 students aged 8 to 18 years showed that deficits in naming speed (in particular, in naming numbers) were the most frequent explanation of math problems in children with DD, followed by deficits in short-term/working memory and planning skills. Deficits in attention were the least frequent. The findings are explained in light of current literature, and suggestions for follow-up research are presented.